Modeling for printed-circuit board simulation. - Balaram, A.
Whereas simulation has long been important in the modeling of ICs, designers have been reluctant to apply it to printed-circuit boards. But an abundance of software is available to speed board design, and it comes without long learning curves or big price tags
Keywords: Board design; Circuit modelling; Printed-circuit boards; Simulation software